INTEREST RATE HIKE AND THE INSTABILITY IN THE U.S. BANKING INDUSTRY - Lai Vo; Huong Le (Applied Finance Letters)
This paper investigates the effect of interest rate changes on the U.S. banks’ performance captured by unrealized losses, investment securities allocation, and deposit withdrawal. We show that a sudden surge in interest rates could lead to massive losses, potentially erasing the market value of a bank's equity capital. We further show that the U.S. banks have switched more available-for-sale securities to held-to-maturity securities to reduce the realized losses. Moreover, such an increase in interest rates could prompt depositors, particularly those with uninsured deposits, to withdraw their funds. These factors pose significant risks to banks, as evidenced by some recent abrupt failures in the U.S. banking sector.